Recent Advances in Medical Statistics - Vargas-De-León, Cruz (IntechOpen, 2022)
This book illustrates the use of complex statistical models in medical and health sciences. The use of these models by researchers contributes to the understanding of more complex processes and thus advances knowledge. The various chapters describe how an ordinal logistic model is applied to disabilities, a model in structural equations to an emergency code, multi-state models for the analysis of time-to-event data and Copula models to agitation-sedation scores, spatial models to epidemiology, and statistical methods to clinical trials and to N-of-1 trial design.